(3cfR GdeWGdH aj aVd GdHjJ GdMQGe hGdTGPQhGf heG aj RjGQI GdbHQ GdTQja ef GdeBQHs - (3GdYOhj GdMeRGhj GdeGdcj, MSf, J (B1303 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj LYd HjJg GdMQGe eKGHI ddfGS hCefG EfG deG cGf GYXe Gdeff GdQHGfjI hGdehGgH GdQMeGfjI Gdhbha Ydi CUhd GdSfI GdeMeOjI GfHYK NGWQ Pj GdgeI GdSGejI s
(3BNQgG (B:s
(3bGd GdeMbb GHf MLQ hCbhd ajg fXQ deG UQM Hg CUMGHfG ef EWdGb fOH LejY eG eQO Ce MVhQg Ce Cg` Cbhd hGdedMX GdXGgQ dG fXQ dCf eY Gdedd GSGAI GdCOH aGdceGd aj GdGfJbGd Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\199s
(3EjVGM Gdecfhf (B2\387s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds